On the Characteristics of Impulse Generators and the Impulse Test of Lightning Arresters - ISSIKI, Teizô (The Journal of the Institute of Electrical Engineers of Japan, 1928)
Characteristics of the impulse generator using the discharge of condenser are described, cons dering the effects of spark potential drop at the discharging gap and capacitance of the voltage measuring device and the test sample shunting the discharge resistance. The results of experiments for impulse voltage are given and explained. Then the performance of the lightning arrester when subject to the ordinary impulse test is compared with its parformance for surge voltage on the transmission system, and it is pointed out that the ordinary method of impulse test often gives the false results for the lightning arrester having considerable capacitance. A new method is devised in which impulse voltage is applied to the lightning arrester under test through an artificial line. This method gives reliable results for the performance of any lightining arrester for surge voltage on the transmission system.